On improving wave energy conversion, part II: Development of latching control technologies. (March 2015) - Sheng, Wanan; Alcorn, Raymond; Lewis, Anthony
Abstract: In the first part of the investigation, a new latching control technology is proposed, and it has been shown that the new latching control technique is capable of greatly improving wave energy conversion in regular waves. In this part of the research, a new analysis technique is developed for studying the latching control technology. A 'time-out' method is developed and employed for 're-packing' the dynamic system, hence the analysis of the latching control technology can be changed from a complete nonlinear dynamics into a simple linear dynamic system, and it is further proven that the 're-packed' dynamic system can be transformed back to frequency domain for further analysis. In the research, we could prove how the phase optimal condition can be attained. Further on, the new latching control technology will be used in irregular waves. Unlike many other latching control technologies, the new latching control does not need the detailed future information. In the development of the technology, we will show how we can obtain the latching duration for irregular waves for improving wave power extraction. As a result, we could remove one barrier in implementing latching control strategy while the wave energy conversion can still be much improved. Highlights: A new 'time-out' technology is developed for studying latching control technologies. Phase optimisation and excitation enlargement achieved in the new latching control. New latching control in irregular wave based on the wave energy period. Damping optimisation for improving power conversion.